THE INFLUENCE OF LIVE STREAMING, PRICE PERCEPTION, AND CUSTOMER REVIEW ON PURCHASING DECISIONS FOR SKINTIFIC PRODUCTS AT THE TIKTOK SHOP - Indri Kurniasari; Muhammad Yani (PT ANTIS INTERNATIONAL PUBLISHER, 2025)
Objective: This study aims to analyze the influence of live streaming, price perception, and customer reviews on consumer purchasing decisions for Skintific products on TikTok Shop. Method: A quantitative research design was implemented, using purposive sampling to target users who had purchased Skintific products through TikTok Shop. Data were collected from 96 respondents, determined using the Rao Purba formula, through questionnaires employing a Likert scale for measurement. The collected data were analyzed using SmartPLS software to evaluate the relationships among the studied variables. Results: The findings demonstrate that live streaming features, consumer price perceptions, and customer reviews each have a significant and positive impact on purchasing decisions. These factors enhance consumer engagement, trust, and confidence in online buying behavior. Novelty: This research contributes to the growing body of e-commerce literature by providing empirical evidence of how TikTok’s interactive features and user-generated content drive consumer purchasing behavior, offering strategic insights for digital marketers in the social commerce environment.